(untitled) (Chimica nella Scuola, 2022)
Articolo tratto da tesi di laurea di Giovanni Polisena, La scuola di oggi e il mondo di domani. Insegnamentodelle scienze, storia e STS, Bologna, Università di Bologna, 2022 Scientific specialism is inevitable, but not in the field of teaching. Science, technology and society (STS) studies’ approach along with the history of science can equip students with the skills to face the complexities of society. The introduction of this teaching approach within upper secondary schools could represent the unifying element missing from the increasingly jagged scientific curricula. At school, it is important to educate students to debate scientific values, because these will determine thepolitical choices and social visions of tomorrow.